2011
DOI: 10.7763/ijapm.2011.v1.29
|View full text |Cite
|
Sign up to set email alerts
|

A Correlative Study of Geomagnetic Storms Associated with Solar Wind and IMF Features During Solar Cycle 23

Abstract: Abstract-A geomagnetic storm is a global disturbance in Earth's magnetic field usually occurred due to abnormal conditions in the interplanetary magnetic field (IMF) and solar wind plasma emissions caused by various solar phenomenon. Furthermore the magnitude of these geomagnetic effects largely depend upon the configuration and strength of potentially geo-effective solar/interplanetary features. In the present study the identification of 220 geomagnetic storms associated with disturbance storm time (Dst) decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…By extension, disturbances in the solar wind, magnetosphere and FDs are triggered 273-2 by the same processes in the Sun. The study of these disturbances is important in our understanding of the dynamics of the solar-terrestrial environment since such activities can potentially result in life threatening issues ranging from satellite damage, communication failure to navigational difficulties (Joselyn & McIntosh 1981;Rathore et al 2011). This underscores the rationale for examining the impact of solar-geomagnetic characteristics on GCR intensity reductions.…”
Section: Introductionmentioning
confidence: 99%
“…By extension, disturbances in the solar wind, magnetosphere and FDs are triggered 273-2 by the same processes in the Sun. The study of these disturbances is important in our understanding of the dynamics of the solar-terrestrial environment since such activities can potentially result in life threatening issues ranging from satellite damage, communication failure to navigational difficulties (Joselyn & McIntosh 1981;Rathore et al 2011). This underscores the rationale for examining the impact of solar-geomagnetic characteristics on GCR intensity reductions.…”
Section: Introductionmentioning
confidence: 99%
“…Perubahan kerapatan elektron tersebut apabila terjadi peningkatan elektron disebut sebagai badai positif sedangkan sebaliknya disebut sebagai badai negatif, dan tidak jarang dijumpai badai positif dan negatif muncul bersamaan tetapi pada lintang yang berbeda [10]. Dengan demikian kejadian badai geomagnet dan badai ionosfer tidak terlepas dari adanya CME, medan magnet antar planet (IMF, Interplanetary Magnetic Field) [11]. Peningkatan energi yang di transfer dari angin surya dan IMF ke dalam magnetosfer menunjukkan intensifikasi arus cincin [12] Terdapat tiga fase pembentukan badai geomagnet, yaitu fase awal, fase utama dan fase pemulihan.…”
Section: Data Dan Metode Penelitianunclassified
“…During an anti-parallel orientation of the interplanetary magnetic field (IMF) to the geomagnetic field lines, solar wind energy, momentum and mass could be transferred into the Earth's magnetosphere, thereby influencing its dynamics and geomagnetic storms. Landmark studies [3][4][5][6][7][8][9] have shown that B z , which is the north-south direction component of the IMF, is a good index that plays a vital role in the reconnection between the solar and terrestrial magnetic fields, leading to additional energy in the magnetospheric flux tube and the geoeffectiveness of geomagnetic storms. A southward B z , fluctuating in the corotating interacting regions (CIRs), is a prerequisite for magnetic reconnection leading to the development of geomagnetic storms [4] whereas, a northward B z rarely leads to storms except during extremely high solar wind speed [5,10].…”
Section: Introductionmentioning
confidence: 99%